2015
DOI: 10.1039/c5cy00353a
|View full text |Cite
|
Sign up to set email alerts
|

Pd–Ag/SiO2 bimetallic catalysts prepared by galvanic displacement for selective hydrogenation of acetylene in excess ethylene

Abstract: 8A series of bimetallic Pd-Ag/SiO 2 catalysts were prepared by galvanic displacement with 9 increasing loadings of Pd on Ag. The catalysts were characterized by atomic absorption 10 spectroscopy, Fourier-transform infrared spectroscopy of CO adsorption and X-ray photoelectron 11 spectroscopy. An actual Pd deposition beyond the theoretical limit for galvanic displacement 12 suggested that the large difference in surface free energy for Pd and Ag resulted in Pd diffusion 13 into the bulk of Ag particles, or Ag d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 52 publications
6
46
0
Order By: Relevance
“…Ranges of 20-40% of C 4+ selectivity have been reported for acetylene hydrogenation, thus evidencing the relevance of this reaction path. [23][24][25][26] For the hydrogenation of acetylene, several intermediates have been postulated based on surface characterization techniques combined, in some cases, with kinetic studies. 18,27,28 The reaction starts by H 2 dissociation and the adsorption of acetylene on the surface; both steps are exothermic.…”
Section: Reaction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Ranges of 20-40% of C 4+ selectivity have been reported for acetylene hydrogenation, thus evidencing the relevance of this reaction path. [23][24][25][26] For the hydrogenation of acetylene, several intermediates have been postulated based on surface characterization techniques combined, in some cases, with kinetic studies. 18,27,28 The reaction starts by H 2 dissociation and the adsorption of acetylene on the surface; both steps are exothermic.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…When the same catalytic process was studied using Pd-Ag/SiO 2 bimetallic catalysts prepared by galvanic displacement during which controlled loadings of Pd were added to the Ag/SiO 2 pre-catalyst, the resulting bimetallic nanoparticles provided lower selectivity to ethene than in the previous case. 26 Experimental and computational studies were reported on the effect of the coverage of the palladium phase with a second metal, in the semi-hydrogenation of acetylene. Zhang and co-workers reported that the optimal Pd@Ag and Pd@Au catalysts (in terms of TOF and selectivity) were those with a coverage of 0.92, obtained using a molar ratio of ca.…”
Section: Dilution Of the Active Phase: Introduction Of Modifiersmentioning
confidence: 99%
“…A more promising methodology to attain stable, isolated Pd sites in a Au matrix for this reaction may involve the inverse of this synthesis technique-that is, deposition of small amounts of Pd onto preformed Au particles. Notably, Zhang et al [40] have demonstrated successful isolation of Pd sites in pre-formed Ag particles through galvanic displacement of Ag by Pd 2? salts.…”
Section: Low Dispersion (Ld) Pd/sio 2 and Au-pd/sio 2 Catalystsmentioning
confidence: 98%
“…They demonstrate very high ethylene selectivity but require elevated temperatures to provide high acetylene conversion and are therefore strongly limited for commercial use. On the contrary, in spite of the high activity, selectivity, and stability of supported monometallic palladium catalysts, they are not sufficient, especially at high acetylene conversions, so the second metal (e.g., Ag, Cu) is introduced to improve catalytic performance [33,57]. It hinders palladium hydride formation and decreases the number of adjacent Pd sites responsible for multiplet adsorption leading to over-hydrogenation of acetylene to ethane and its oligomerization to higher hydrocarbons (green oil) [57,58].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, in spite of the high activity, selectivity, and stability of supported monometallic palladium catalysts, they are not sufficient, especially at high acetylene conversions, so the second metal (e.g., Ag, Cu) is introduced to improve catalytic performance [33,57]. It hinders palladium hydride formation and decreases the number of adjacent Pd sites responsible for multiplet adsorption leading to over-hydrogenation of acetylene to ethane and its oligomerization to higher hydrocarbons (green oil) [57,58]. The Pd-Ag bimetallic catalysts have been found to be most efficient and are successfully employed on an industrial scale [59].…”
Section: Introductionmentioning
confidence: 99%